2013
DOI: 10.1111/ahg.12026
|View full text |Cite
|
Sign up to set email alerts
|

Thirty-Nine Novel Neurofibromatosis 1 (NF1)Gene Mutations Identified in Slovak Patients

Abstract: SummaryWe performed a complex analysis of the neurofibromatosis type 1 (NF1) gene in Slovakia based on direct cDNA sequencing supplemented by multiple ligation dependent probe amplification (MLPA) analysis. All 108 patients had café-au-lait spots, 85% had axilary and/or inguinal freckling, 61% neurofibromas, 36% Lisch nodules of the iris and 31% optic pathway glioma, 5% suffered from typical skeletal disorders, and 51% of patients had family members with NF1.In 78 of the 86 (90.7%) index patients our analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 72 publications
3
26
1
Order By: Relevance
“…4%: Valero et al (2011), 89.5%: Nemethova et al (2013), 96.3%: Sabbagh et al (2013)]. Hence, the performance of the presently reported protocol was comparable with that of the direct capillary sequencing methods.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…4%: Valero et al (2011), 89.5%: Nemethova et al (2013), 96.3%: Sabbagh et al (2013)]. Hence, the performance of the presently reported protocol was comparable with that of the direct capillary sequencing methods.…”
Section: Discussionsupporting
confidence: 51%
“…Comparison of the distributions of nonsense, splice-site variants, and missense mutations in the Japanese population versus the northern European population, as reported by Messiaen et al (2000), Nemethova et al (2013), Sabbagh et al (2013), andValero et al (2011), revealed no statistically significant differences among the groups ( p = 0.203 using the Fisher exact test for countable data).…”
Section: Mutation Detectionmentioning
confidence: 72%
“…2000; Nemethova et al. 2013). In two patients, we obtained clinical evidence of segmental NF1, probably due to mosaicism (NF1_40 and NF1_122).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, higher detection rates were possible only with a multistep protocol, when analyses of DNA and RNA were integrated (Nemethova et al. 2013; Sabbagh et al. 2013) 95% was reached by Messiaen et al.…”
Section: Discussionmentioning
confidence: 99%
“…These include neurofibromatosis type 1, Rubinstein-Taybi syndrome, Cornelia de Lange syndrome, and Kleefstra syndrome [Roelfsema et al, 2005;Russo et al, 2012;Nemethova et al, 2013;Schwaibold et al, 2014]. These cases provide evidence that a partial duplication of ZEB2 could similarly result in a haploinsufficient condition.…”
Section: Discussionmentioning
confidence: 86%